Measures on two-component configuration spaces - Finkelshtein, D.L. (Condensed Matter Physics, 2009)
We study the measures on the configuration spaces of particles of two types. Gibbs measures on such spaces are described. Main properties of corresponding relative energy densities and correlation functions are considered. In particular, we show that a support set for such Gibbs measure is the set of pairs of non-intersected configurations. Ми вивчаємо мiри на просторах конфiгурацiй двох типiв. Описано гiбсовськi мiри на таких просторах. Розглянуто основнi властивостi вiдносних енергiй та кореляцiйних функцiй. Зокрема, показано, що такi гiбсовськi мри зосередженi на парах конфiгурацiй, якi не перетинаються.